Development of Computer Simulation Algorithm for Trajectory Analysis of Objective Function of Dynamic Object Models for Unmanned Aerial Vehicles - Poltavsky, Alexandr; Akhobadze, Gurami (2021 International Russian Automation Conference (RusAutoCon), 2021)
This paper examines modern approaches and the simulation method for multi-level and multi-connected information management systems based on the objects composed of numerical method algorithms. The concept aims at the improved computer modeling of data acquisition and control systems of multifunctional automated robotic systems, in particular, for many objects of multipurpose unmanned aerial vehicles. It is applicable at the initial stages of their conceptual properties development. The application of certain numerical methods, algorithms and software for information modeling allows initially considering and assessing their practical value for the preliminary stages of testing and design of up-to-date objects. The latter are used for data acquisition and control systems. The research work results can be used for controlling the tethered unmanned aerial vehicle employed as an air-borne platform to solve various national and economic problems.